Complete genome sequence, metabolic profiling and functional studies reveal Ligilactobacillus salivarius LS-ARS2 is a promising biofilm-forming probiotic with significant antioxidant, antibacterial, and antibiofilm potential - Patra, Sinjini; Pradhan, Biswaranjan; Roychowdhury, Anasuya (Frontiers in Microbiology, 2025)
BackgroundProbiotics restore microbial balance and prevent gut-inflammation. Therefore, finding out novel probiotic strains is a demand. As gut-microbe, benefits of Ligilactobacillus salivarius (LS) are established. However, strain-specific detailed studies are limited. Here, we illustrate probiotic attributes of novel LS-ARS2 for its potential application as food-supplement and/or therapeutic to improve gut-health.MethodsWhole genome sequencing (WGS) and phylogenetic analysis confirm the strain as LS. To establish probiotic properties, acid-bile tolerance, auto-aggregation, cell-surface-hydrophobicity, biofilm-formation, and adhesion-assays are performed. To ensure safety attributes, antibiotic-susceptibility, hemolytic, DNase, trypan-blue, and MTT assays are done. ABTS, DPPH, superoxide, hydroxyl free radical scavenging assays are used to determine anti-oxidant potential. Antibacterial assays, including co-culture assay with pathogen and pathogenic biofilm-inhibition assays, are performed to explore antibacterial efficacy. To characterize metabolic-profile of LS-ARS2-derived cell-free-supernatant (CFS), HRMS analysis are carried out. Consequently, WGS-analyses predict potential molecular associations related to functional outcomes.ResultsWe find LS-ARS2 a remarkable fast-growing strain that shows acid and bile tolerance (>60% survival rate), indicating promising gut-sustainability. High auto-aggregation capacity (>80%), robust cell-surface hydrophobicity (>85%), and adhesion efficacy to Caco-2 cells illustrate significant potential of LS-ARS2 for gut colonization. Fascinatingly, LS-ARS2 is able to form biofilm within 24 h (p < 0.0001), rare among LS strains, indicating the potential of the strain for efficient stay in the gut. The strain ensures safety attributes. LS-ARS2-WGS analysis recognizes probiotic-specific determinants, predicts genomic stability, identifies orthologous-clusters for diverse functions, and predicts metabolites and bacteriocins. HRMS-studies with LS-ARS2-CFS further validate the presence of diverse beneficial metabolites with antimicrobial and immunomodulatory potential. LS-ARS2 shows significant antioxidant properties in ABTS (>60%), DPPH (>10 U/mL), superoxide (>70%), and hydroxyl free radical scavenging assays (>70%). Further, LS-ARS2 shows antimicrobial activities against Gram-positive Methicillin-resistant Staphylococcus aureus (MRSA) and Gram-negative multidrug-resistant clinical strains enterotoxigenic Escherichia coli, Vibrio cholerae, and Shigella flexneri. Anti-Salmonella effect of LS-ARS2 is prominent (p < 0.0001). Most interestingly, LS-ARS2-CFS inhibits MRSA-biofilm (p < 0.0001), again rare among LS strains.ConclusionLS-ARS2 is a novel, fast-growing, biofilm-forming probiotic with significant antioxidant, antibacterial, and anti-biofilm potentials, suggesting the promising applications of LS-ARS2 for combating pathogenic biofilms and improving gut-health. However, further in vivo studies would facilitate their potential applications.